Acute Methamphetamine and Benzylpiperazine Decrease Aggression- Related Behavior in Late Adolescent Male Rats - N.L. Johnson, Hamish; N. Hughes, Robert (Current Psychopharmacology, 2013)
The effects on aggression in late adolescent male rats of acute administration (via intraperitoneal injection) of 10 or 20 mg/kg of the designer drug, benzylpiperazine (BZP), were assessed in comparison with 1 or 2 mg/kg of methamphetamine (MA). The two drugs are very similar in their behavioral and neurochemical effects. Aggression was measured with the resident/intruder test of aggression which involves recording eight forms of behavior in response to an intruder rat being placed in the resident drug-treated rat’s cage. Both drugs led to often dose- and specific drug-related changes in seven of the eight measures that were indicative of decreased (rather than increased) aggression which may have arisen from hyper-vigilance, increased activity or heightened fear/anxiety i.e., decreases in an aggressive posture, chasing and sniffing the intruder and self-grooming, accompanied by increases in adopting an alert position, rearing on hind legs and avoiding the intruder. It was concluded that acute treatment with neither MA nor BZP increased aggression. As revealed in earlier research with adult rats, both drugs proved to be remarkably similar in their overall behavioral effects.
Keywords: Anxiety